2012
DOI: 10.1002/ijc.27557
|View full text |Cite
|
Sign up to set email alerts
|

18F‐FDG‐PET evaluation of treatment response to neo‐adjuvant therapy in patients with locally advanced rectal cancer: A meta‐analysis

Abstract: The purpose of this meta-analysis was to evaluate the utility of positron emission tomography (PET) using fluor-18-deoxyglucose (FDG) to predict the response of rectal cancer to neo-adjuvant therapy. All previously published studies on the role of FDG-PET in predicting the response of rectal cancer to neo-adjuvant therapy were collected. Pooled sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were calculated using statistical software. A total of 28 studies, compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 38 publications
1
15
1
1
Order By: Relevance
“…Our results are consistent with accumulating evidence, including a recent meta-analysis on the predictive role of metabolic response to preoperative RCT in LARC, that the early evaluation of response during treatment is more promising than evaluation after completion of therapy [39]. Previously reported results on the predictive value of 18 F-FDG PET/CT in patients with LARC after and during preoperative treatment are not uniform.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are consistent with accumulating evidence, including a recent meta-analysis on the predictive role of metabolic response to preoperative RCT in LARC, that the early evaluation of response during treatment is more promising than evaluation after completion of therapy [39]. Previously reported results on the predictive value of 18 F-FDG PET/CT in patients with LARC after and during preoperative treatment are not uniform.…”
Section: Discussionsupporting
confidence: 94%
“…A significant tumor downsizing and downstaging, as well as a reduction of the risk for local recurrence and longer survival have been observed as a result of PRCT [13]. Within this context, 18 F-FDG PET imaging has been demonstrated as an interesting predictive tool [4]. Indeed, correlations between the pathological tumor response after PRCT and the standard uptake value (SUV) decrease within the tumor have been demonstrated in several studies [59].…”
mentioning
confidence: 99%
“…Although early information on tumor response may be important for the choice of the most appropriate therapeutic strategy and was promising in a recent metanalysis [38], we did not find a useful role of early metabolic assessment as a possible surrogate biomarker of pathological response. On the contrary, in the posttherapy evaluation we found that both the final absolute value of SUVmax and the percentage reduction of the baseline value may predict pCR in LARC; in fact, SUV3 and RI (1–3) were significantly lower in patients with pCR as compared to non-pCR ones and, in univariate analysis, both parameters appeared to be significant predictive factors of pCR.…”
Section: Discussionmentioning
confidence: 51%